Estimating systemic risk for non-listed euro-area banks - Robert F. Engle; Tina Emambakhsh; Simone Manganelli; Laura Parisi; Riccardo Pizzeghello (European Central Bank (ECB), 2023)
The systemic risk measure (SRISK) by V-Lab provides a market view of the vulnerability of financial institutions to a sudden downturn in the economy. To overcome the shortcoming that it cannot be applied to non-listed banks, SRISK characteristics of listed banks are mapped on balance sheet information. Systemic risk tends to be higher for banks that are larger, less profitable and have lower equity funding. Balance sheet information provides a surprisingly good approximation of SRISK for non-listed banks, when compared with banks' capital depletion from the EU-wide stress testing exercises in 2018 and 2021. The proposed methodology can usefully complement the more thorough overview provided by traditional stress tests, providing supervisors the option to evaluate the systemic risks of the banking system at a higher frequency and at a fraction of the costs.
Keywords: G21; G28; G1; 330; Systemic risk; stress testing; banks' balance sheet information content